Implementation of a Virtual Acoustic Room in the Digital Music Mixing Process - Noval Ardhian Pranata; Mochammad Usman Wafa (Jurnal Ragam Pengabdian, 2026)
Advancements in digital technology have driven a shift in music production from physical studios toward Digital Audio Workstation (DAW)–based production supported by virtual acoustic rooms capable of digitally simulating spatial characteristics. This phenomenon enables the engineering of spatial perception, depth, and sound quality without reliance on real acoustic spaces, while also supporting production efficiency, the formation of sonic identity, and the integration of traditional and modern electronic music. This study employs a descriptive qualitative approach with a case study method to examine the application of virtual acousticrooms in the digital music mixing process, with the research subjects consisting of works by Enggar Ardiandi and a comparative mixing result of the song Melangkah by audio practitioner Ridho. Data were collected through literature review, work analysis, observation of the mixing process, and evaluations by listeners and practitioners, then analyzed descriptively and analytically by linking field findings with relevant theories, while data validity was ensured through source triangulation. The results indicate that the application of virtual acoustic rooms in the works of Enggar Ardiandi and Ridho positions virtual reverb as a primary element in shaping spatial perception, depth, and sonic cohesion in digital music mixing, with a comprehensive and immersive approach in Enggar’s work and a selective and controlled approach in Ridho’s work, underscoring the flexibility of this technology in accommodating aesthetic needs, workflow efficiency, and overall audio quality enhancement.